Relationship between History of Caesarean Section Delivery and Placenta Previa: A Literature Review - Lulu Farida (Pena Medika : Jurnal Kesehatan, 2025)
Complications during pregnancy and childbirth in the form of bleeding are the main cause of maternal mortality. One case of bleeding is placenta previa. The cause of placenta previa has not been explained, but the occurrence of placenta previa is often associated with a history of cesarean delivery. The purpose of writing this article is to compare the results of research that has been done with theories related to the relationship between cesarean section delivery and the occurrence of placenta previa. This article is a literature review in the form of literature compiled by utilizing secondary data from various publications related to the relationship between a history of cesarean delivery and the occurrence of placenta previa. The results of several studies show a strong correlation between a history of cesarean section and the occurrence of placenta previa in subsequent pregnancies, but one study found no correlation between a history of cesarean section and placenta previa. The theory explains that fibroid tissue from uterine wall wounds created during cesarean section affects the vascularization of placental implantation. Another theory also states that women who have undergone two or more cesarean sections are at higher risk of experiencing placenta previa. This literature can be used as a consideration regarding the importance of choosing delivery in pregnant women according to indications because cesarean delivery can be a risk factor for placenta previa in subsequent pregnancies, which can affect maternal mortality rates